If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1 + n = -20 Solving -1 + n = -20 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + n = -20 + 1 Combine like terms: -1 + 1 = 0 0 + n = -20 + 1 n = -20 + 1 Combine like terms: -20 + 1 = -19 n = -19 Simplifying n = -19
| -11x+10=-12x+8 | | 9x+3y+1y-0.9x= | | 10y-17=6y-12 | | -6x-10=38 | | 9x^2+18x-39=0 | | -10=h-6 | | -9+13x=11-x | | 5.39x+16=29.0521+4x | | 11-5x+3=2x+4-3x | | -13m+14-11=7(-m+13)+2 | | 15x+2=9x+22 | | 7(7y+17)=16+8(5y+5) | | 4x^5-22x^3-80x=0 | | -6p+7=-5(2p+13) | | 10(2)-3x=15 | | -16w=8(-w+6) | | r^2-2r^2+3r^2= | | (2dc)(4c^2d^5)= | | -20j+3j+19=-9(3j+18)-19 | | 10(0)-3x=15 | | 7(-r-15)+9r=9r | | (3x-3)*2x=84 | | 5(-b+4)=-(20-5b) | | 10(1)-3x=15 | | -20-18g=2(-15g+20) | | -8(-2q+15)-1=6-5q+20 | | 2*(4x+2)=16+2x | | -9.53-0.4k=-0.7k-12.8 | | 3(x+1)-(2x+6)=-9 | | -17.4h-12.96=0.61-17.3h-12.36 | | -18.4s+2.08=19.51-16.3s | | 210=-7(-7m+5) |